The Impact of Trachomatous Trichiasis on Quality of Life: A Case Control Study. - Esmael Habtamu; Tariku Wondie; Sintayehu Aweke; Zerihun Tadesse; Mulat Zerihun; Zebideru Zewudie; Wondimu Gebeyehu; Kelly Callahan; Paul M Emerson; Hannah Kuper; Robin L Bailey; David C W Mabey; et al. (PLoS Neglected Tropical Diseases)
Background Trachomatous trichiasis is thought to have a profound effect on quality of life (QoL), however, there is little research in this area. We measured vision and health-related QoL in a case-control study in Amhara Region, Ethiopia. Methodology/principal findings We recruited 1000 adult trichiasis cases and 200 trichiasis-free controls, matched to every fifth trichiasis case on age (+/- two years), sex and location. Vision-related quality of life (VRQoL) and health-related quality of life (HRQoL) were measured using the WHO/PBD-VF20 and WHOQOL-BREF questionnaires. Comparisons were made using linear regression adjusted for age, sex and socioeconomic status. Trichiasis cases had substantially lower VRQoL than controls on all subscales (overall eyesight, visual symptom, general functioning and psychosocial, p<0.0001), even in the sub-group with normal vision (p<0.0001). Lower VRQoL scores in cases were associated with longer trichiasis duration, central corneal opacity, visual impairment and poor contrast sensitivity. Trichiasis cases had lower HRQoL in all domains (Physical-health, Psychological, Social, Environment, p<0.0001), lower overall QoL (mean, 34.5 v 64.6; p<0.0001) and overall health satisfaction (mean, 38.2 v 71.7; p<0.0001). This association persisted in a sub-group analysis of cases and controls with normal vision. Not having a marriage partner (p<0.0001), visual impairment (p = 0.0068), daily labouring (p<0.0001), presence of other health problems (p = 0.0018) and low self-rated wealth (p<0.0001) were independently associated with lower overall QoL scores in cases. Among cases, trichiasis caused 596 (59%) to feel embarrassed, 913 (91.3%) to worry they may lose their remaining eyesight and 681 (68.1%) to have sleep disturbance. Conclusions/significance Trachomatous trichiasis substantially reduces vision and health related QoL and is disabling, even without visual impairment. Prompt trichiasis intervention is needed both to prevent vision loss and to alleviate physical and psychological suffering, social exclusion and improve overall well-being. Implementation of the full SAFE strategy is needed to prevent the development of trachomatous trichiasis.